Oil Prices and Economic Activity in Nigeria: An Asymmetric Cointegration and Threshold Analysis: Array - Alenoghena, Raymond; Arhotomhenla Aghughu, Adolphus (Acta Universitatis Danubius. Œconomica, 2022)
Oil price fluctuation greatly affects the economy of oil producing net-exporting small open economies of developing countries. This study investigates the nonlinear relationship between oil price volatility and economic growth in Nigeria, covering the period 1981 to 2019. The nonlinear autoregressive distributed lag (NARDL) model is adopted to establish the asymmetric cointegration status of oil price volatility and GDP growth. The switching point between the variables is estimated using the threshold regression approach. The results from the NARDL analysis reveal that the relationship between oil price volatility and economic growth is cointegrated in the long run and has an asymmetrical relationship. Furthermore, the threshold regression investigation indicates that the switching point for the oil price in the relationship with economic growth is US$48.263 per barrel. Hence, whenever oil price falls below the threshold, there is a negative effect on the country’s economic growth. Therefore, the study recommends that the government take advantage of oil export earnings and make some savings whenever oil price goes above the threshold. The savings can be used to assist in developing the other sources of foreign exchange earnings and sustain the country’s development effort.